The indiscriminate use of antibiotics in the ICU (Research, Society and Development, 2022)
The indiscriminate use of antibiotics is one of the biggest public health problems in the world because it generates antimicrobial resistance and one of the factors of this generate this problem is the excessive prescription of antibiotics in ICU. Thus, the objective of this study is to address the in ICU indiscriminate use of antibiotics and the methodology chosen was an integrative literature review of recent studies on the subject, having as inclusion criteria studies for the development of research listing in scientific databases, dating from 2017 to 2022, in Portuguese and English, a bibliographic search was carried out between April and May 2022, using scientific journal articles as a data source and the following keywords as inclusion characters: Global health; Microbial drug resistance, Antibiotics in ICU, making a table with studies that deal with the subject, bringing their objectives and main results. It has been researched that the proper use of antibiotics in medical practice has been a point of discussion, as well as many studies in recent years, and they must be correctly implemented to bring benefits both in prophylactic and therapeutic capacity. But when these drugs are not used properly, especially routinely in patient care, there may be unnecessary exposure and possible risks of these agents; thus, it is necessary promotion of strategies, the improvement of communication skills with patients and the conduction of more studies about the subject.